(3ebGdI aj MQcGJ GdchGcHs - (3GdeHGQc Hf CMeO Hf GdeHGQc Hf ehghH GddNej GdEQHdj, GdeYQha HGHf GdeSJhaj,J (B637 (3g` s
(3ChdgG (B:s
(3GdeHMK GdChd ai GdTeS hajg aUhd GdaUd GdChd ai JYjjf LOGhd CYde Cf GdeHMK GdTeS UMGFa efgG s
(3BNQgG (B:s
(3hHGbi GdeQGcR Ydi fXGFQ gPg HGdOQLI hGdObjbI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B170s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs